SINGLE NUCLEOTIDE SOMATIC VARIANTS OF Tp53 GENE IN WIDESPREAD NEOPLASMS OF CANIS FAMILIARIS - R. Saif; A. R. Awan; L. Lyons; B. Gandolfi; M. Wasim (Journal of Animal and Plant Sciences, 2018)
Sequence diversity of Tp53 gene was analyzed in dog tumors to have an insight of accumulated somatic mutations in 18 samples belongs to 7 different types of cancers. Nine different polymorphic sites were observed in exon 3, 4 and 5, while 32 polymorphic sites are observed in intron 3, 4 and 9. Most of these alterations are heterozygous, locus c.76 in exon 3 is transversion with homozygous (G) variant in one of the mammary and CTVT samples, which is missense in nature and alter the leucine amino acid to valine. Similarly, c.356 locus in exon 5 is homozygous ( C), that is also a transversion, which changed the lysine residue to threonine. Most of the observed cancer samples are heterozygous in intronic regions of this gene. Current study of sequence variations of cancerous somatic cells in the aforementioned gene confirm the involvement of this gene in cancer pathways and might serve as potential molecular diagnostic and prognostic marker for these cancer types in Canis familiaris and may be helpful for other animal species as well. mutations being considered potential markers for cancer
Keywords: Tp53variants; Dog tumor; Canis familiaris cancer.